2023
DOI: 10.1152/japplphysiol.00428.2023
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability to eccentric exercise training is diminished with age in female mice

Cory W. Baumann,
Colleen S. Deane,
Timothy Etheridge
et al.

Abstract: The ability of skeletal muscle to adapt to eccentric contractions has been suggested to be blunted in older muscle. If eccentric exercise is to be a safe and efficient training mode for older adults, preclinical studies need to establish if older muscle can effectively adapt and if not, determine the molecular signatures that are causing this impairment. The purpose of this study was to quantify the extent age impacts functional adaptations of muscle and identify genetic signatures associated with adaptation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Old rats, conversely, had a gradual drop in maximum torque throughout the entire training period, which was accelerated by adding faster eccentric contractions (which are typically more damage-inducing (44,45)) starting at day 7. A recent study comparing old and young mice observed similar findings, with young mice becoming 20-36% stronger but old mice becoming 18% weaker following 5 weeks of high-intensity eccentric training 1 day/week (97). One explanation in the present study may be the lower pre-training SSN in old rats compared to young.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Old rats, conversely, had a gradual drop in maximum torque throughout the entire training period, which was accelerated by adding faster eccentric contractions (which are typically more damage-inducing (44,45)) starting at day 7. A recent study comparing old and young mice observed similar findings, with young mice becoming 20-36% stronger but old mice becoming 18% weaker following 5 weeks of high-intensity eccentric training 1 day/week (97). One explanation in the present study may be the lower pre-training SSN in old rats compared to young.…”
Section: Discussionmentioning
confidence: 61%
“…To that point, Rahman et al (102) observed that impaired ECM remodelling limited the regenerative response following damage to the tibialis anterior induced by cardiotoxin in old compared to young mice. Furthermore, Baumann et al (97) compared gene profiles of young and old mice following 5 weeks of eccentric training, and found that while young and old mice both exhibited upregulation of genes associated with sarcomere organization and assembly, only old mice exhibited upregulation of genes associated with ECM remodelling, likely indicative of fibrosis. This remodeling of the local connective tissue environment in old may blunt the ability for a mechanical signal to be transduced into a biochemical response (8,107), limiting serial sarcomerogenesis.…”
Section: Discussionmentioning
confidence: 99%